Renal Pathologic Findings in TAFRO Syndrome: Is There a Continuum Between Thrombotic Microangiopathy and Membranoproliferative Glomerulonephritis? A Case Report and Literature Review - Leurs, Amélie; Gnemmi, Viviane; Lionet, Arnaud; Renaud, Loïc; Gibier, Jean-Baptiste; Copin, Marie-Christine; Hachulla, Eric; Hatron, Pierre-Yves; Launay, David; Fajgenbaum, David; Terriou, Louis (Frontiers in Immunology, 2019)
Background: TAFRO syndrome is a clinical subtype of idiopathic multicentric Castleman disease (iMCD) that is characterized by thrombocytopenia, anasarca, fever and/or elevated serum C-reactive protein, renal dysfunction, and organomegaly. Case presentation: A 28-year-old woman with fever, weight gain of 13kgs, lower extremity edema, hepatosplenomegaly, and multicentric peripheral lymphadenopathy was referred to our center. Laboratory investigations revealed anemia, thrombocytopenia, creatinine at 1.19 mg/dL and hypoalbuminemia at 33 g/L. Proteinuria was measured at 2 g/day including albuminuria at 1.5 g/day. Urinary sediment examination found leukocyturia at 44,000/mL and hematuria at 645,000/mL. Vascular endothelial growth factor (VEGF) level was elevated. A cervical lymph node biopsy found features consistent with the mixed histopathological subtype of iMCD. A renal biopsy revealed a membranoproliferative glomerulonephritis (MPGN) pattern. We initiated 3 days of methylprednisolone pulse-therapy at 1000mg per day, followed by prednisone 1mg/kg/day and evolution was favorable. Review of literature: 19 iMCD patients with TAFRO syndrome had undergone a renal biopsy: 8 cases with author’s diagnosis consistent with MPGN-like and 11 cases of thrombotic microangiopathy (TMA)-like glomerulopathy without fibrin thrombi in glomerular capillaries or arterioles and without typical biological signs. Clinical, biological, and outcome characteristics were similar between the cases described as having MPGN and TMA-like presentation. After a thorough review of histopathological descriptions for each case, MPGN lesions seems to be the consequences of chronic glomerular endothelial injury in persistent TMA. We suspect that VEGF and IL-6 play a key role in the physiopathology of the spectrum of renal involvement from TMA-like to MPGN observed in TAFRO syndrome. Conclusion: We present a Caucasian iMCD patient with TAFRO syndrome with renal insufficiency secondary to MPGN, which might be secondary to a chronic TMA-like disease. We suspect that there is a continuum between TMA and MPGN lesions in TAFRO syndrome favored by VEGF and IL-6.